AMPK Activation by Metformin Suppresses Abnormal Extracellular Matrix Remodeling in Adipose Tissue and Ameliorates Insulin Resistance in Obesity - Luo, Ting (Diabetes, 2016)
Fibrosis is emerging as a hallmark of metabolically dysregulated white adipose tissue (WAT) in obesity. Although adipose tissue fibrosis impairs adipocyte plasticity, little is known about how aberrant extracellular matrix (ECM) remodeling of WAT is initiated during the development of obesity. Here we show that treatment with the antidiabetic drug metformin inhibits excessive ECM deposition in WAT of ob/ob mice and mice with diet-induced obesity, as evidenced by decreased collagen deposition surrounding adipocytes and expression of fibrotic genes including the collagen cross-linking regulator LOX. Inhibition of interstitial fibrosis by metformin is likely attributable to the activation of AMPK and the suppression of transforming growth factor-β1 (TGF-β1)/Smad3 signaling, leading to enhanced systemic insulin sensitivity. The ability of metformin to repress TGF-β1-induced fibrogenesis is abolished by the dominant negative AMPK in primary cells from the stromal vascular fraction. TGF-β1-induced insulin resistance is suppressed by AMPK agonists and the constitutively active AMPK in 3T3L1 adipocytes. In omental fat depots of obese humans, interstitial fibrosis is also associated with AMPK inactivation, TGF-β1/Smad3 induction, aberrant ECM production, myofibroblast activation, and adipocyte apoptosis. Collectively, integrated AMPK activation and TGF-β1/Smad3 inhibition may provide a potential therapeutic approach to maintain ECM flexibility and combat chronically uncontrolled adipose tissue expansion in obesity.